KEPUTUSAN PEMBELIAN DI PENGARUHI OLEH PROMOSI PENJUALAN PADA KLINIK KECANTIKAN DI GARUT - hari mulia (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The phenomenon of the emergence of skin beauty treatments in Garut is growing rapidly along with consumer awareness to take care of their skin. However, in the last 3 years there has been a decline in customers for beauty treatments. In this regard, a research was conducted at a beauty clinic in Garut with the title "Purchase Decisions Affected by Sales Promotion at Beauty Clinics in Garut". The research method used in this study is the causal method. The population in this study was 1,225 customers and the sample used was 92 people using simple random sampling technique. The data collection used is a questionnaire, the analytical technique used in this research is instrument test (validity test and reliability test), correlation coefficient test, coefficient of determination test and hypothesis testing. The results of data processing obtained using SPSS Version 26 software for windows, that the instrument used in this study was declared valid and reliable because it had a value greater than r table of 0.205. From the correlation coefficient test results obtained information that sales promotion has a very strong influence with a value of 0.959 with a coefficient of determination of 91.9%, and based on hypothesis testing there is a positive and significant effect with a significance value of 0.000 <0.005 while t count 31.918> t table 1.66.